Survival and prognostic analysis of preoperative indicators in patients undergoing surgical resections with rhabdomyosarcoma. Issue 43 (23rd October 2020) - Jin, Hongyu; Zhang, Man; Zhou, Hui; Zhu, Shiyu; Hu, Chenggong
Abstract : Abstract: Several preoperative blood and biochemical parameters are associated with postoperative survival in many kinds of tumors. The aim of this study is to study the predictive value of several routine preoperative blood and biochemical parameters on the prognosis patients with rhabdomyosarcoma (RMS). We retrospectively recruited 55 patients diagnosed with RMS and had surgery at West China Hospital, Sichuan University between January 2010 and December 2018. Baseline characteristics of the patients, tumor features, surgery details, and values of several examinations were extracted. A long-term follow-up was conducted by phone call. A novel statistical analysis was subsequently carried out to look for the relationship of preoperative parameters and patients' prognosis. The ROC analysis showed an area under curve (AUC) of 0.608, 0.620, 0.626, 0.591, and 0.518 for neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), monocyte to lymphocyte ratio (MLR), lactic dehydrogenase (LDH), and alkaline phosphatase (ALP) respectively, and the cut-off value of 2.843, 162.961, and 0.239 for NLR, PLR, and MLR respectively. The survival analysis showed that certain blood and biochemical parameters could cause differences in overall survival (OS) ( P  = .005 for NLR, P  = .005 for PLR, and P  = .007 for MLR) and progression free survival (PFS) ( P  = .029 for NLR, P  = .008 for PLR, and P  = .013 for MLR). Several preoperative blood and biochemical parameters are novel prognostic factors in RMS patients. Specifically, a higher NLR, PLR, and MLR value will predict a statistically shorter OS and PFS. In the future, surgeons should care more about NLR, PLR, and MLR values and several other parameters in patients' preoperative normal blood and biochemical tests to predict the postoperative conditions.